PENGARUH KUALITAS PELAYANAN AKADEMIK TERHADAP TINGKAT KEPUASAN MAHASISWA (Studi Kasus di Fakultas Teknik Prodi Teknik Industri Unisbank Semarang) - Flady Dian Pratama; Eddi Indro Asmoro (Jurnal Ilmiah Dinamika Teknik, 2020)
This research aims to measure the quality of academic service to the level of student satisfaction. Students ' complaints are based on the brain-strorming in small discussions of each generation. This research was conducted on the Faculty of Engineering Progam Industrial Engineering Study of Stikubank University of Semarang. This Research uses quantitative approaches. The population in this study is a student of the Faculty of Engineering Progam Industrial Engineering Study of Stikubank Semarang University. In this study because the population was relatively limited, the entire population in this study was made into samples (census samples), so the samples in this study amounted to 69 people. It is based on the theory expressed by (Arikunto, 1993),